Plan de negocios, mediante el estudio de mercado, para proponer la creación del complejo turístico “La Montañita”, en la ciudad matriz del cantón Shushufindi - Ramón Jiménez, Byron Alcides (2016)
The research was conducted in the Canton Shushufindi in its parent city, highlighting the need for residents and tourists in the area have not a suitable place where they can indulge healthily as resorts in the sector did not meet the needs of visitors. For this reason the business plan was designed by the market research, to propose the creation of the resort the "MONTAÑITA" the same that contributed positively to life and daily routine of people form. The research process that was used for the project was the situational analysis of the area to know the market where the company was developed by analyzing sectors, including infrastructure of basic services sector, natural, cultural, demographic analysis, economic diagnosis, socio-cultural analysis. Situational feasibility study was considered and the business plan was developed through a market study for which were used: survey data where the services were implemented was obtained, competition and suppliers determined. With this information the design of the resort which determined the functionality of their areas and activities which featured the project and its proper distribution was developed. The design of the complex was guided to the standards required by the MUNICIPAL GOVERNMENT AUTONOMO decentralized Shushufindi Canton because this is their competition. It prevailed especially efficient customer service, and its revenue, the success of the Tourist Complex.